Allogeneic stem cell transplantation in treatment of chronic myeloid leukaemia – current approach in tyrosine kinase inhibitors era - Gil, Lidia; Lewandowski, Krzysztof; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2010)
Introduction of tyrosine kinase inhibitor (TKI), imatinib, revolutionized therapy of chronic myeloid leukemia (CML) and caused considerable reduction in the numbers of allogeneic stem cell transplantation (allo-HSCT) in this disease. Based on current data allo-HSCT remains however the only curative method for CML. Current indication for allo-HSCT in CML are discussed in the paper. Evidence supporting decision concerning transplant procedure (conditioning and source of hematopoietic stem cells), postransplant monitoring on molecular level and treatment of relapse with donor lymphocyte infusion and TKI are presented. Identification of patients with the risk of progression and TKI resistance are an important issue and should be base for decision when and how to perform transplantation.